Apresiasi Siswa terhadap Batik Tanjung Jabung Barat dalam Pembelajaran Budaya - Yenni Rahmah; Jupriani; Syeilendra (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to describe students’ appreciation of Batik Tanjung Jabung Barat in cultural learning among ninth-grade students at SMP Negeri 12 Tanjung Jabung Barat. The focus of the study includes three main aspects: knowledge, attitudes, and student engagement. This study employs a descriptive approach with a mixed descriptive model, emphasizing qualitative data as the primary data supported by simple quantitative data obtained through questionnaires, observations, and interviews. The research subjects consisted of 109 students selected using purposive sampling techniques. Data analysis was conducted using descriptive qualitative methods through the stages of data reduction, data display, and conclusion drawing. The questionnaire results indicate that the overall level of students’ appreciation falls into the "good" category with an average of 75%. In detail, the attitude aspect obtained the highest percentage at 82% (very good), the knowledge aspect at 74% (good), and the engagement aspect at 69% (moderate). The results of data analysis show that although students feel proud of wearing batik, their understanding of the philosophical meaning of local batik motifs remains limited. This study concludes that culture-based learning grounded in local wisdom has successfully fostered positive student attitudes; however, there is still an imbalance in the aspects of knowledge and engagement, thus requiring more contextual, interactive, and experience-based learning strategies to optimize students’ appreciation. This study is limited to one school and uses a descriptive approach, so the results cannot be widely generalized. Therefore, future research is recommended to involve a larger sample size and to develop practice-based learning strategies to improve students’ knowledge and engagement more effectively.